(untitled) (Physical Education, Health and Social Sciences, 2026)
Ankle injuries are among the most common musculoskeletal issues in badminton players due to quick directional changes and high lower-limb demand. Despite badminton’s popularity in Pakistan, limited research has examined ankle injury prevalence and associated risk factors among recreational players. To determine the prevalence of ankle injuries and identify its associated risk factors among recreational badminton players in Peshawar. A cross-sectional study was conducted among 387 recreational badminton players from three academies in Peshawar. Data was collected using on the Modified Nordic Musculoskeletal Questionnaire (MNMQ), including items on demographics, Prevalence, training characteristics, warm-up practices, previous injuries, footwear, stretching habits, and strength/balance training. The prevalence of ankle injuries was assessed, and chi-square tests were applied to evaluate associations between injuries and potential risk factors. The prevalence of ankle injuries was 45.2%. Significant associations were found between ankle injuries and dominant leg (p = .000), playing experience (p = .000), warm-up practices (p = .000), stretching/ankle mobility exercises (p = .000), previous 12-month injury history (p = .000), ankle support/taping (p = .000), and regular strength/balance training (p = .000). No significant association was observed with gender (p = .260), footwear (p = .318), or fatigue (p = .148). Ankle injuries are highly prevalent among recreational badminton players in Peshawar. Insufficient warm-up routines, lack of mobility training, poor neuromuscular conditioning, and previous injuries significantly increased risk. Preventive strategies emphasizing proper warm-up, stretching, and balance/strength training may reduce injury incidence.